Everything I Know about Marketing I Learned From Google - Goldman, Aaron (McGraw-Hill, 2010)
Want Market Share? Google It! "Google is a once-in-a-generation company. Aaron Goldman has written an essential book that goes beyond telling us how Google became so important to explaining why the revolution it's leading will affect everyone in media and marketing."--Brian Morrissey, Digital Editor, Adweek "An insightful tour of the elements that have made Google successful combined with a usable guide on how to apply this learning to your business." -Rishad Tobaccowala, Chief Strategy & Innovation Officer, Vivaki About the Book You know you've hit it big when your name becomes a verb-and no one knows that better than Google. In just over 10 years, Google has become the world's most valuable brand, consistently dominating its category and generating $6 billion in revenue per quarter. How does Google do it? In a word: marketing. You may not think Google does much marketing. Indeed, it doesn't do a lot of what has traditionally been viewed as marketing. But in today's digital world, marketing has taken new shape-and Google is at the cutting edge. In Everything I Know about Marketing I Learned from Google, digital marketing expert Aaron Goldman offers 20 powerful lessons straight from Google's playbook. Taking you deep into the inner workings of the Googleplex (which are simpler than you think), Goldman provides the knowledge and tools you need to build and grow your brand (which is also simpler than you think). Along the way, he shows how Google's tactics are being used by a wide range of successful corporations, from Apple to Zappos. Key principles include: Tap into the Wisdom of Crowds: Get the signals you need directly from your customers Keep It Simple, Stupid: Craft messages people can grasp in a nanosecond and pass along Don't Interrupt: Join the conversation- but avoid disrupting it Act Like Content: Provide value, not sales pitches Test Everything: Take no detail of your program for granted; you can always improve Show Off Your Assets: Distribute your brand everywhere The beauty of it all is that these Googley lessons can be applied to every aspect of marketing, in organizations of any size. Whether you run a PR department in a multinational corporation or serve as the sole marketer in a small business, these tactics work. In its mission to "organize the world's information," Google has rewritten the book on marketing. Use Everything I Know about Marketing I Learned from Google to remake your own organization's marketing-and engage mo ...